Unlocking early literacy: a needs analysis to evaluating the necessity of Malay reading modules in preschool education - Arulmozhi Narayanasamy; Anis Norma Mohamad Jaafar; Nadia Shahira Amiruddin; Julianty Idris (Journal of Education and Learning (EduLearn), 2026)
This article investigates the critical issue of reading skill acquisition among preschoolers in Malaysia, particularly in the context of educational disruptions resulting from the COVID-19 pandemic. Through a qualitative study employing semi-structured interviews with five Sekolah Jenis Kebangsaan Tamil (SJKT) preschool educators, the research identifies several significant challenges: a lack of specialized reading modules for non-native Malay speakers, communication barriers, need for differentiated instruction and more engaging and interactive content. Furthermore, the study underscores the vital role of parental involvement in reinforcing literacy development at home. These findings highlight the urgent need for a structured and culturally relevant reading module, such as the proposed Saya Boleh Baca (I-SaBoBa) module, specifically designed to address the needs of Malaysian preschool children. The study concludes that addressing these gaps is essential for fostering early literacy skills, which are critical for future academic achievement. The proposed module seeks to mitigate these challenges by equipping educators and parents with effective tools to enhance children’s reading proficiency within a supportive and engaging environment.